(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
Educational assignments are a crucial component of the learning process, serving to reinforce acquired knowledge, monitor students’ academic activities, and assess their mastery of key competencies. In modern education, traditional instructional tasks must be complemented by creative and imaginative learning activities that foster independent, critical, and innovative thinking skills. This study explores the didactic significance of integrating creative and imaginative tasks in teaching history at higher education institutions. Drawing on theoretical analysis and practical classification of learning assignments, the paper identifies key types of creative and imaginative tasks, their functional purposes, and their role in enhancing students’ analytical, problem-solving, and historical reasoning abilities. The research highlights the necessity of non-standard, innovative approaches in history instruction, moving beyond chronological narration to the analysis of causes, consequences, and alternative historical scenarios. The findings demonstrate that consistent use of creative and imaginative assignments increases student engagement, stimulates independent research, and fosters the production of original educational outputs such as diagrams, models, and project designs. Ultimately, these tasks contribute to the development of students’ competencies in generating multiple solutions to complex historical problems, thereby preparing them for the demands of the contemporary labor market.